An Evaluation of Risk Culture at a Regional Owned Enterprise in South Kalimantan: A Case Study of PT. Air Minum ABC - Dzakiyah Nur Azmie; Viska Anggraita (Greenation International Journal of Economics and Accounting, 2025)
Mayor Regulation of ABC Number 93 of 2019 emphasizes the obligation to implement risk management within the Government of XYZ City, including regional owned enterprises such as PT. Air Minum ABC. The purpose of this study is to evaluate the implementation of risk culture at PT. Air Minum ABC (Perseroda) using the 2012 framework developed by The Institute of Risk Management (IRM), through a combined approach of risk personality (Risk Type Compass), individual ethics (Moral DNA), and organizational perspective (Risk Culture Aspect Model). Primary data were collected through a survey involving 94 employees and in-depth interviews with the heads of risk management and internal audit, supported by secondary data obtained from internal documents of PT. Air Minum ABC. This study shows that PT. Air Minum ABC (Perseroda) has established a relatively strong foundation of risk culture based on the IRM 2012 framework, with an organizational score of 62 points, indicating a medium level of maturity. The Risk Type Compass (RTC) analysis reveals a dominance of Deliberate, Prudent, and Wary risk types among the majority of employees, while the Moral DNA results indicate strong ethical values in the dimensions of obedience, reason, and care, particularly among managerial staff and employees in the mature age group. The Internal Audit Division stands out in both personality and ethical aspects. At the organizational level, the aspects of Tone at the Top and Informed Risk Decision received the highest scores, whereas Accountability, Risk Resources, and Rewarding Appropriate Risk Taking still require strengthening. These findings underscore that building a strong risk culture depends not only on systems, but also on individual personality profiles and ethical values that shape collective behavior across all levels of the organization.